Malignant Diffuse-Type Tenosynovial Giant Cell Tumor in the Subcutaneous Tissue of the Midthigh: A Report of a Rare Tumor in an Unusual Location - Omar Salem; Khalid Kurdi; Amani Joudeh; Ahmad Al-Dhafiri; Zahra Alkhunaizi; Emad Al Absi (Case Reports in Orthopedics)
Malignant TS-GCT is an extremely rare and aggressive tumor with only few cases published in the literature, due to the small number of cases is not completely understood and is diagnostically challenging. Although surgical treatment is the primary treatment modality, there is no consensus regarding adjuvant treatment. Regardless of mode of treatment, the tumor still caries unfavorable prognosis. In this paper, we reviewed the literature for cases of malignant TS-GCT. We also would like to present an additional case of malignant TS-GCT that was found in an unusual location in subcutaneous tissue of the midthigh.